#### Answer

$x\approx 5.24$ and $x\approx -0.76$.

#### Work Step by Step

The given equation is
$\Rightarrow 3x^2-18x+12=0$
Divide each side by $3$.
$\Rightarrow x^2-6x+4=0$
Find the value of $(\frac{b}{2})^2$.
Substitute $-6$ for $b$.
$=(\frac{-6}{2})^2$
Simplify.
$=(-3)^2$
$=9$
Add $5$ to each side of the equation.
$\Rightarrow x^2-6x+4+5=0+5$
Simplify.
$\Rightarrow x^2-6x+9=5$
Write the left side as the square of a binomial.
$\Rightarrow (x-3)^2=5$
Take the square root of each side.
$\Rightarrow x-3=\pm \sqrt{5}$
Add $3$ to each side.
$\Rightarrow x-3+3=\pm\sqrt{5}+3$
Simplify.
$\Rightarrow x=\pm\sqrt{5}+3$
The solutions are $x=\sqrt{5}+3\approx 5.24$ and $x=-\sqrt{5}+3\approx -0.76$.